'What' Is Happening in the Dorsal Visual Pathway. Issue 10 (October 2016) - Freud, Erez; Plaut, David C.; Behrmann, Marlene
Abstract : The cortical visual system is almost universally thought to be segregated into two anatomically and functionally distinct pathways: a ventral occipitotemporal pathway that subserves object perception, and a dorsal occipitoparietal pathway that subserves object localization and visually guided action. Accumulating evidence from both human and non-human primate studies, however, challenges this binary distinction and suggests that regions in the dorsal pathway contain object representations that are independent of those in ventral cortex and that play a functional role in object perception. We review here the evidence implicating dorsal object representations, and we propose an account of the anatomical organization, functional contributions, and origins of these representations in the service of perception. Trends: In both human and non-human primates, the posterior portion of the dorsal pathway generates object-based representations that are unrelated to action planning or execution. Patients with extensive lesions to the ventral pathway still generate object representations in the dorsal pathway, and evince perceptual sensitivity to object structural information. Neuropsychological investigations with patients, and lesion studies with non-human primates, have demonstrated that a lesion to the posterior part of the parietal cortex leads to perceptual deficits, particularly in 3D perception and in the perception of structure from motion.